Islam Dan Tata Nilai Kehidupan Di Era Modern - Agus Toni (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Understanding of Islam as a religion of rahmatan lil alamin must be based on its role in building, patterning and directing humans to be able to understand changes in context both in relation to muamalah, siyasah and worship. With the basis of Islamic teachings elasticism along with the value of huminism, its existence in the same way as humans will be an atmosphere that is able to protect Islam from all forms of intention to undermine and weaken systemically and massively confront the Islam itself. To reach the final point, the departure of mindset and basic thinking is needed with an emphasis on the basics of tasamuh and tawazun on the value of human collectivity along with a set of rules or culture that are so complex that the community is able to translate Islam as a religion that is not only a metaphysical religion but also has a high value of rationality. Age development has consequences for changes in human mindset and attitude. Such a situation will provide the value of its own space for Islam to provide an umbrella or legality so that people in behaving are not considered out of or violating Islamic teachings. The substance in the application of Islamic law and Islamic teachings is the reason for the acceptance of Islamic teachings in all world lines in good condition. Openness in accepting the changing times marked by globalization inspires those who wrestle in the world of Islamic law and muafassir to be able to understand humans in terms of conformity of text and context. Islamic elasticity in the face of changing times is a sign that the prosperity of the values of Islamic teachings can be felt wherever people are in funds with whatever cultural style they are engaged in. The diversity of ways of misrepresenting problems in Islamic law gives space to the public that the concept of Islam in solving problems has a flexible value. Keywords, Islam, Culture, Religion and Culture